2013
DOI: 10.1186/1477-7525-11-136
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between health-related quality of life, and acute care re-admissions and survival in older adults with chronic illness

Abstract: BackgroundAustralia’s ageing population means that there is increasing emphasis on developing innovative models of health care delivery for older adults. The assessment of the most appropriate mix of services and measurement of their impact on patient outcomes is challenging. The aim of this evaluation was to describe the health related quality of life (HRQoL) of older adults with complex needs and to explore the relationship between HRQoL, readmission to acute care and survival.MethodsThe study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
(48 reference statements)
0
21
1
3
Order By: Relevance
“…19,[32][33][34] However, acute care studies have been based on small sample sizes ranging from 45 to 938 patients. The extent to which the relationship between functional status and all-cause readmissions is generalizable to the US population remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…19,[32][33][34] However, acute care studies have been based on small sample sizes ranging from 45 to 938 patients. The extent to which the relationship between functional status and all-cause readmissions is generalizable to the US population remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy and chronically ill community-dwelling older adults, it has been demonstrated that higher HRQOL is associated with longer survival and lower hospitalization rates. 7,8 In acutely admitted older medical patients, HRQOL and its association with outcomes are especially relevant, because these individuals are often extremely vulnerable. Within 3 months of acute hospital admission, 20% to 30% have died, and 30% of those still alive have to adapt to permanent functional impairment.…”
mentioning
confidence: 99%
“…10 Higher CCI scores indicate a greater comorbidity burden, and higher scores have been linked to higher readmission rates. 11 It was noted that study patients with a pharmacy benefi t group had a higher CCI score ( …”
Section: Patient Characteristicsmentioning
confidence: 99%